Peripartum depression: does risk versus diagnostic status impact mother-infant bonding and perceived social support? - Hare, Megan M. (Depress Anxiety, 2020)
BACKGROUND: Peripartum depression (PND) impairs mother-infant boding and perceived social support, yet limited research has examined if women at-risk for PND also experience impairment. We examined if pregnant women at-risk for PND, women with PND, and healthy comparison women (HCW) differed in their mother-infant bonding and social support. As PND is highly comorbid with anxiety, we also examined if peripartum anxiety impacted postpartum diagnosis of PND. METHODS: 144 pregnant women at-risk for PND or euthymic were assessed twice antepartum and twice postpartum. We utilized regression models to examine the impact of PND risk group status and diagnostic status on mother-infant bonding and perceived social support postpartum. We conducted a sensitivity analysis using a generalized estimating equations model to determine if anxiety (Hamilton Anxiety Rating Scale, HAM-A) across all four time points was associated with postpartum diagnosis of PND. RESULTS: Women at-risk for PND experienced significantly worse mother-infant bonding compared to HCW (p=.03). Women diagnosed with PND experienced significantly worse mother-infant bonding and social support compared to HCW (p=.001, p=.002, respectively) and to those who were at-risk for but did not develop PND (p =.02, p =.008, respectively). HAM-A severity at each visit was associated with PND diagnosis status, where each increase in HAM-A was associated with 15% increased odds of being diagnosed with PND postpartum. CONCLUSIONS: Both women at-risk for PND and those with PND experience worse mother-infant bonding. Peripartum anxiety should also be assessed as it represents a marker for later PND.